Effect of environmental enrichment on the surface temperature, skin lesion score and behaviour during transportation of pigs - Crone, C.; Martins, R. A.; Lippi, I. C.C.; Caldara, F. R.; Oliveira, G. F.; Garcia, R. G.; Calado, C. A.; Bevilacqua, A.; Morais, H. B. (My University, 2019)
The aim of the study was to evaluate the environmental enrichment effect during transport of pigs on the surface temperature (ST), skin lesion score (LE) and behaviour, considering as an enrichment the creation of a familiar environment between the housing facilities and the transport vehicle. Two experiments were conducted: the first during transport of the Piglets Production Unit to the nursery and the second during transportation of animals from the Finisher Unit to the slaughterhouse. The animals (n = 250, Exp I and n = 120, Exp II) were distributed in a completely randomised design to five treatments: T1 - control without environmental enrichment; T2 - use of enrichment objects in the truck; T3 - familiar environment using lavender aroma; T4 - familiar environment using music; T5 - familiar environment using truck noise. Treatments were applied at the housing facility five days before transportation and during transportation. The ST of the skin was evaluated by an infrared thermal imager and the skin LE by observation (after transport). The ST of the skin after transport from the Piglets Production Unit to the nursery and from the Finisher Unit to the slaughterhouse was smaller for swine that received the treatment with music. There was no effect of treatments on skin LE in both experiments. Piglets from experiment I exposed to music, had less agonistic behaviour compared to the other treatments. Creating a familiar environment for pigs through the use of music can be promising in improving animal welfare during transport.
Keywords: Music therapy; Surface temperature; Swine; Thermography; Welfare